Consensus-based Recommendations for Research Priorities Related to Interventions to Safeguard Patient Safety in the Crowded Emergency Department - Fee, Christopher (2011)
This article describes the results of the Interventions to Safeguard Safety breakout session of the 2011 Academic Emergency Medicine (AEM) consensus conference entitled “Interventions to Assure Quality in the Crowded Emergency Department.” Using a multistep nominal group technique, experts in emergency department (ED) crowding, patient safety, and systems engineering defined knowledge gaps and priority research questions related to the maintenance of safety in the crowded ED. Consensus was reached for seven research priorities related to interventions to maintain safety in the setting of a crowded ED. Included among these are: 1) How do routine corrective processes and compensating mechanism change during crowding? 2) What metrics should be used to determine ED safety? 3) How can checklists ensure safer care and what factors contribute to their success or failure? 4) What constitutes safe staffing levels / ratios? 5) How can we align emergency medicine (EM)-specific patient safety issues with national patient safety issues? 6) How can we develop metrics and skills to recognize when an ED is getting close to catastrophic overload conditions? and 7) What can EM learn from experts and modeling from fields outside of medicine to develop innovative solutions? These priorities have the potential to inform future clinical and human factors research and extramural funding decisions related to this important topic.